Merton-McCall Reader - Ray City Community Library, Ray City Community Library (Ray City School, 1937)
Merton-McCall Reader; At Work and Play, 1937. Laidlaw Brothers Publishing. Ray City community Library, 1936-ca. 1960 series. Ray City community Library Collection.
Merton-McCall Reader; At Work and Play, 1937. 1 electronic record (PDF), 1.97 GB (2,119,473,634 bytes).
Keywords: Berrien County (Ga.); Ray City (Ga.); Ray City School; Schoolbooks; Vintage Textbooks